فعالية إستراتجية قوّة اثنين في تعليم معارة الاستماع ومهارة الكتابة في مدرسة مفتاح العلوم الابتدائية الإسلامية لامونجان - Ningrum, Amaliyah Herawati Puji (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
ABSTRACT The purpose of this study was to know the use, to know supporting and inhibiting factors and to know the effectiveness of the power of two strategy in listening skill and writing skill learning at Miftahul Ulum islamic elementary school Lamongan. This study uses a qualitative approach and quantitative approach. This study uses the experimental method, the type of design is pre-experimental design. with a one-group pretest-posttest design model. Data collection techniques in the form of tests, interviews and observation. The research subjects were all fourth grade students of Miftahul Ulum islamic elementary school Lamongan. The results of this study indicate that the application of the power of two strategy in listening skill learning is effective. Evidenced in the average value of students. Average score from the pretest value of 66.79 and the posttest value of 82.04. And from the results of the paired sample t-test, the t table value 8,006 is greater than the t tabel value 2,052, which concludes that is rejected and is accepted. So it can be said that there is an effectiveness of the power of two strategy in listening skill and writing skill learning at Miftahul Ulum islamic elementary school Lamongan. مستخلص البحث أهداف البحث هم لتعريف استخدام إستراتجية قوة اثنين، ولتعريف عوامل الداعمة والعائقة إستراتجية قوة اثنين، ولتعريف فعالية إستراتجية قوة اثنين في تعليم مهارة الاستماع ومهارة مهارة الكتابةفي مدرسة مفتاح العلوم الابتدائية الإسلامية لامونجان. استخدم هذا البحث المدخل النوعي والكمي الوصفي. طريقة تجريبية مع نوع التصميم pra-experiment design، بتصميم مجموعة واحدة باختبارالقبلي والبعدي (one-group pretest-posttest design). طريقة جمع البيانات هم الاختبار، مقابلة وملاحظة. المبحوث في هذا البحث الجامعي يعني تلاميذ في الفصل الرابع مدرسة مفتاح العلوم الابتدائية الإسلامية لامونجان. نتائج هذا البحث أن استخدام إستراتجية قوة اثنين (The Power Of two) في تعليم مهارة الاستماع ومهارة الكتابة فعلية. قيمة المتوسط من متوسط ​​قيمة اختبار القبلي 66.79 ومتوسط ​​قيمة اختبار البعدي 82.04. من حصّل الاختبار Paired Sampel T-Test أن ظهر قيمة (t hitung) 8.006 و (t tabel) 2 ،052 والتي توضح أن قيمة (t hitung) أكبر من قيمة (t tabel). هذا يدل على فرضية مرفوض و مقبول. لذلك تم كان فعالية إستراتجية قوة اثنين (The Power Of Two) في تعليم مهارة الاستماع ومهارة الكتابة في مدرسة مفتاح العلوم الابتدائية الإسلامية لامونجان. الكلمات الإشارية : إستراتجية قوة اثنين، مهارة الاستماع، مهارة مهارة الكتابة